STRATEGI PROMOSI PROGRAM UNGGULAN TAHFIDZ DI MADRASAH IBTIDAIYAH NEGERI 1 KENDAL - Nur Astuti, Qorina Alfada; Miftahul Munir; Syukron Jazuli (STIT Bustanul 'Ulum Lampung Tengah, 2025)
One form of religious education that has received special attention in recent years is the tahfidz program, which focuses on memorizing the Qur’an. At Madrasah Ibtidaiyah Negeri (MIN) 1 Kendal, the tahfidz program has been implemented as a flagship initiative integrated into the broader educational curriculum. This program aims not only to enhance students’ memorization of the Qur’an but also to shape students into religious individuals with strong character. This study used a qualitative method to explore the promotional strategies of the tahfidz program at MIN 1 Kendal and to identify the supporting and inhibiting factors. The findings revealed that the promotional strategies align with the four elements of the promotion mix: advertising, sales promotion, personal selling, and public relations. Advertising was carried out through social media such as Instagram, YouTube, TikTok, and the school’s website, while sales promotion included student performances at events like akhirussanah and PKP. Personal selling involved communication through teachers and the school’s media team (GEMI), who managed and shared content both online and directly. Meanwhile, public relations included partnerships with external institutions such as FUSPAQ and PPTQ Ash-Shiddiqie to support both regular and advanced tahfidz programs. Supporting factors included the use of digital platforms, parental enthusiasm, strong school leadership, and qualified teachers. However, challenges remain in terms of human resource limitations, time constraints, and varied student abilities in memorization.